2021
DOI: 10.2478/mgrsd-2020-0046
|View full text |Cite
|
Sign up to set email alerts
|

From post-communist democratic laissez-faire to prevention of territorial fragmentation: tightening the rules of municipal splits in Central and Eastern Europe after 1990

Abstract: The article discusses municipal boundary changes in Central and Eastern Europe, concentrating on the heavily under-researched phenomenon of municipal splits. The first part describes the basic facts of municipal secessions in the region analysed. The second part presents a model explaining the national and municipal level factors behind the variation in the occurrence of successful split initiatives. It distinguishes between national institutional settings, economic, identity (cultural) and local political fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…As Swianiewicz (2020) concludes in his literature review, several hundred empirical studies on amalgamations exist—but at the time of writing, he only found four analyzes of municipal break‐ups. Subsequently, in an ambition to build on and extend Erlingssons' (2005) model to answer why peripheral parts of larger municipalities would wish to start a secession campaign, Swianiewicz (2021) singled out three drivers—all of them, of course, a result of intra‐municipal geographical tensions. In part inspired by the literature on secessions from nation states, these drivers have been dubbed the economic push (Buchanan 1991; Hogen‐Esch 2001), the cultural push (e.g., Danielson 1976), and the political push (Horowitz 1985; Lijphart 1984).…”
Section: Theory Previous Studies and Expectationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As Swianiewicz (2020) concludes in his literature review, several hundred empirical studies on amalgamations exist—but at the time of writing, he only found four analyzes of municipal break‐ups. Subsequently, in an ambition to build on and extend Erlingssons' (2005) model to answer why peripheral parts of larger municipalities would wish to start a secession campaign, Swianiewicz (2021) singled out three drivers—all of them, of course, a result of intra‐municipal geographical tensions. In part inspired by the literature on secessions from nation states, these drivers have been dubbed the economic push (Buchanan 1991; Hogen‐Esch 2001), the cultural push (e.g., Danielson 1976), and the political push (Horowitz 1985; Lijphart 1984).…”
Section: Theory Previous Studies and Expectationsmentioning
confidence: 99%
“…Given how relatively common they are, de-mergers constitute an under-researched phenomenon. As Swianiewicz (2020) concludes in his literature review, several hundred empirical studies on amalgamations exist-but at the time of writing, he only found four analyzes of municipal break-ups. Subsequently, in an ambition to build on and extend Erlingssons' ( 2005) model to answer why peripheral parts of larger municipalities would wish to start a secession campaign, Swianiewicz (2021) singled out three drivers-all of them, of course, a result of intra-municipal geographical tensions.…”
Section: Place-based Discontent-the Contextmentioning
confidence: 99%
“…Boundary changes are regulated by various procedures (modes), and the choice of procedure always involves dilemmas about balancing local autonomy and central control [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Procedures for changing municipal boundaries in Canada and Europe contrast starkly with those in the US and are generally characterized by the concentration of considerable power in the hands of the state [22].…”
Section: Introductionmentioning
confidence: 99%
“…The issue of boundary changes is widely discussed, although it mainly concerns changes at the municipal level and demonstrates several trends. In Europe, it was the consolidation wave of the 1960s and 1970s under the umbrella of "economies of scale" [24], the fragmentation of the 1990s conducted as part of decentralization efforts, mainly in the post-Soviet bloc countries [2,21]. In the early 2000s, new consolidation reforms occurred, on the one hand, as a way to effectively absorb European funds in the "Europe of Regions" [25] and, on the other, in response to the global economic crisis [26].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, this study is part of the research on the impact of territorial-administrative reorganizations on the capacity to deliver services at the local level or on local democracy (see: Swianiewicz (ed. ), 2010;Soukopova et al, 2014;Steiner et al, 2016;Ebinger et al, 2019;Swianiewicz, 2021).…”
Section: Introductionmentioning
confidence: 99%